Peran Kekuatan Merek bagi UMKM MoriGe : Sebagai Perlindungan Hukum dan Mendukung Keberlanjutan Bisnis - Widya Yuniati Siregar; Debora Debora (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
MoriGe is a Micro, Small and Medium Enterprise (MSME) located in Oebufu Village, Kupang City, East Nusa Tenggara, which was established in 2020. This MSME has a main focus on the production of processed food and beverages made from Moringa and Sorghum, two local food commodities that are known to have high nutritional value and extraordinary health benefits and are still rarely found in the market but these plants thrive in the land of NTT. Through an Innovation-based approach, MoriGe continues to be committed to processing Moringa and Sorghum into Quality products that are not only delicious but also provide health benefits. MoriGe products made from Moringa and Sorghum are designed to meet the needs of the modern market for healthy food with local flavors. This commitment is in line with MoriGe’s goal to increase the competitiveness of local products in the global market while supporting the economic development of surrounding communities, especially local farmers, and also participating in programs to reduce stunting in NTT, so that MoriGe has more value as a brand in the eyes of a wide audience.